The Legal Regime for Consumer Protection under the Nigerian Jurisprudence: An Examination - Obumneme-Okafor, N.J. (African Journal of Education,Science and Technology (AJEST), 2013)
The law of consumer protection envisages the safety of the consumer in all ramifications irrespective of the area involved and the nature of the consumer in question. This is so because lack of this protection has consequential effect on the life of the citizens not minding the person denied the protection. The significant position occupied by this protection in the life of a nation can never be over emphasized. It thus calls for the examination of the available legal frame work for the protection of the consumer. A close scrutiny of he frontline legislations will be carried out to ascertain whether their provisions as they are will, if effectively implemented, accord adequate protection to the consumer. In doing so, the setbacks embedded in these provisions which impede consumer protection will be highlighted. Lastly the paper will attempt to proffer the way out of these setbacks and hitches to ensure that the average Nigerian is accorded the requisite protection